2011
DOI: 10.1002/ar.21414
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Castration and Hormone Replacement on the Cross‐Sectional Area of Pubococcygeus Muscle Fibers in the Female Rat

Abstract: In this study, we analyzed the effect of ovariectomy and gonadal hormone replacement on the cross-sectional area of pubococcygeus (Pcm) fibers. It was found that in comparison to intact animals, ovariectomized animals [for 2 or 6 weeks] had an increased cross-sectional area average in Pcm fibers. Ovariectomy also reduced the percentage of fibers with smaller cross-sectional area. In ovariectomized animals after 4 weeks of hormone replacement with an empty Silastic capsule or filled with testosterone propionate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
2
4
0
Order By: Relevance
“…17 Serum estradiol levels and the age of rabbits could explain the CSA response herein and in the previous study. Otherwise, findings herein, and from other rat studies, 27,28 confirm estrogen can differentially affect individual PFM. Although, in rats, the Pcm myofiber CSA seems more responsive to estrogens that induce a CSA reduction.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…17 Serum estradiol levels and the age of rabbits could explain the CSA response herein and in the previous study. Otherwise, findings herein, and from other rat studies, 27,28 confirm estrogen can differentially affect individual PFM. Although, in rats, the Pcm myofiber CSA seems more responsive to estrogens that induce a CSA reduction.…”
Section: Discussionsupporting
confidence: 63%
“…Although, in rats, the Pcm myofiber CSA seems more responsive to estrogens that induce a CSA reduction. 27,28 Overall, we believe these findings shed light on the understanding of menopausal hormone therapy on PFM morphometry. 29 Reduced estradiol levels undermine bladder contractility in rabbits.…”
Section: Discussionmentioning
confidence: 66%
“…In rat, the organization of pelvic skeletal muscles, coccygeus, iliocaudalis, and pubocaudalis, are anatomically similar to human PFMs. 24,25 Furthermore, we recently reported that with respect to major architectural parameters, rat PFM design is similar to human. 26 Rat has also been shown to be a reliable model for the study of pregnancy-related changes in cervix, vagina, and vaginal supportive structures.…”
mentioning
confidence: 89%
“…[4][5][6][7][8] Estrogen replacement therapy is commonly prescribed for the treatment of pelvic dysfunctions; however, its efficacy is controversial. 9 The effect of the estrogen administration on periurethral skeletal muscles has been previously approached, 6,8,10,11 although some issues regarding their estrogenic sensitivity remain to be addressed. Estrogens influence mass, contractile properties, damage/repair processes and the expression of ER in hindlimb skeletal muscles.…”
Section: Introductionmentioning
confidence: 99%